Kemampuan Guru Ipa Dalam Menyusun Rencana Pelaksanaan Pembelajaran Kurikulum 2013 Kelas Viii Di SMP Se-Kabupaten Jepara Tahun Pelajaran 2014/2015 - ANGGARINI, DIEN MEILA, Dra. Hariyatmi, M.Si (2015)
Competence of teachers are influence on student achievement. The teachers who doesn't mastering their material of Science, unreliable to their works and responsibility as a profesional teacher. A profesional teacher must have at least four main skills in actual appearance, for example is planning a learning process. Based on writer's observations the teachers still hasn't creating lesson plans before the learning or they create it just to complete their competence administration. The purpose of this study are to obtain informations about Science teachers competency in creating eighth grade Junior High School lesson plans of the school yeas 2014/2015 in Kabupaten Jepara as well as the suitability of the implementation of lesson plans in learning. This study is descriptive qualitative based on case studies. Data collection techniques using documentation, observation and interview. The result showed there are: (1) Science teachers competency in creating lesson plans in eighth grade Junior High School in Kabupaten Jepara by 80,49% was on significant category. There had disadvantage in preparing learning materials (70,83%), learning objectivities (64,58%), choose the learning source (35,42%) and also teaching methods (62,5%). (2) The suitability of the implementation of lesson plans in learning reached 92,08% but still had disadvantage in applying Integrated Science teaching (77,08%) and closing the learning (75%). keyword: curriculum 2013, lesson plans, teacher competency